Non Conventional Approaches for Management of Drug Addiction and CNS Disorders (Global Journal of Medical Research, 2020)
Addiction is a serious and widespread disorder that has devastating consequences for individuals and society. However, the existing treatment for addiction is moderately effective at best. In recent years, the researchers have renewed their interest in the effectiveness of classic hallucinogens for clinical uses such as treating addictions and other behavior-related health issues. In the present work, we tried to review both pharmacological mechanisms of actions and the recent researches done on the use of classical hallucinogens in treating addiction. Also, some selective review related to other relevant researches was done, for suggesting prospectus of future research. The classic hallucinogen showed extraordinary record for safety in clinical research. Also, with the limited understanding of the clinically important impacts of classic hallucinogens, there are many opportunities for future research which may contribute novel knowledge and help in treating addiction. This review provides the scientific literature related to the use of classic hallucinogens and the related mechanism of action of psychedelic in treating drug addiction.
Keywords: addiction; natural psychedelics; hallucinogens